Klasifikasi Perbankan dengan Pendekatan CART dan MARS - Otok, Bambang Widjanarko (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2005)
Monitoring system have been come to need for performance of to banking in the future, as well as to know strategy implication with complex problems. However, that system if broken down into simple terminology, every individual can start to comprehend foreign exchange market and using it as a monetary investment appliance for the future.